Correlation between job burnout, psychological status, and job satisfaction among anesthesiologists in the post-COVID-19 era: a cross-sectional study in China - Xuemeng Chen; Rui Zhou; Xianjie Zhang; Jia Han; Feng Ju; Yukai Zhou; Leqiang Xia (Frontiers in Public Health)
BackgroundBurnout is a prevalent issue among healthcare professionals, particularly anesthesiologists, with significant repercussions for patient safety, personal well-being, and institutional efficiency. The post-COVID-19 era has introduced additional psychological and socioemotional stressors, which individuals perceive differently. This study aims to assess burnout levels among anesthesiologists in this era, explore its relationship with psychological status and job satisfaction, and propose potential intervention strategies.MethodsFour hundred electronic questionnaires were distributed to anesthesiologists licensed in 2024 with over 1 year of clinical experience. Three hundred twenty-six responses were collected, yielding an 81.5% response rate. The survey instruments included the Maslach Burnout Inventory-Human Services Survey (MBI-HSS), The Depression, Anxiety and Stress Scale – 21 Items (DASS-21), and Minnesota Satisfaction Questionnaire-Short Form (MSQ-SF). Descriptive statistics and adjusted linear regression were employed to analyze the data and examine the relationships between burnout, psychological status, and job satisfaction.ResultsThe study revealed a high prevalence of burnout, with 30.67% of participants at high risk and 24.85% exhibiting burnout syndrome, resulting in an overall burnout rate of 55.52%. Demographic factors were significantly associated with burnout (p < 0.05). Anesthesiologists aged 30–34 reported higher levels of anxiety and depression, while those aged over 35 showed lower levels of depersonalization and higher personal accomplishment (p < 0.001). Job satisfaction was inversely correlated with burnout (p < 0.001). Psychological status was positively correlated with burnout (p < 0.001). Multiple linear regression analysis explained 55.00% of the variance in burnout, with anxiety, stress, and intrinsic and extrinsic satisfaction as significant predictors (p < 0.05).ConclusionBurnout is widespread among anesthesiologists in the post-COVID-19 era, with burnout levels strongly associated with mental health and job satisfaction. Increased negative emotions and reduced job satisfaction contribute to higher burnout. Addressing the well-being of anesthesiologists, fostering a supportive work environment, and improving compensation mechanisms could alleviate burnout and enhance the quality of medical practice.